(untitled) (The Agriculturists, 2020)
The focal objective guided the present study was to investigate the impact of labor migration on rural livelihood. Pakundiaupazila under Kishoregonj district was purposively selected as the locale of the study. Three villages viz. Narandi, Hossendi and Patuabhanga were randomly selected. A sample consisting of 80 respondents, having at least one migrant agricultural labor was selected following stratified proportionate random sampling technique. Quantitative data were collected by the researchers using a structured interview schedule through face to face interview method. Qualitative data were collected through group discussion and direct observation methods. Statistics like range, mean, percentile and rank order were employed throughout the study. Majority (54.5%) of the household owners fell under old age group; 53.2 percent belonged to the group of primary level of education; 56.3 percent had medium family; 78.8 percent families were nuclear; more than half (51.0%) of them belonged to medium income category; greater part (55.2%) of them had medium contact with the sources of information; 50.1 percent of the respondents had low organizational participation; and 50.0 percent of them showed high cosmopoliteness. Majority of migrant workers (46.7%) migrated in Middle East and Dhaka city (25.3). Major causes of labor migration were higher income possibilities, job security, social status, major types of migration were rural-urban, migration to other country and seasonal migration. Vital negative impacts of labor migration on agriculture were: decreased family labor; dependency on remittance; and increased vulnerability difficult situation. Vibrant positive impacts of labor migration were observed on financial capital (increased remittance flow and total household income) followed by physical (enriched household gadgets and real properties possession), human (improved skills in agricultural practices and enhanced competency in managing farm production) and social capitals (enhanced social relation and developed social network)while negative impact was observed on natural capital (decreased agricultural land status and natural vegetation). Hiring labor, change in cropping pattern and agricultural transformation were the major ways of coping up with labor shortage in agricultural production. The Agriculturists 2020; 18(1) 66-80